Letter to Jane Tolmach; from George Grimes - George Grimes:::::: (1963)
Letter to Jane Tolmach, from George Grimes (Chairman & Board of Trustees) sent on December 4, 1963. This letter contains a calendar of dates and services in which divisions from Mental State hospitals in California will be inspected by.